2008
DOI: 10.1016/s1658-3655(12)60030-2
|View full text |Cite
|
Sign up to set email alerts
|

Tracing of Gram-negative antibiotic-resistant bacteria in hospitals final effluent at Al-Madinah Al- Mounwwarah

Abstract: The final effluent for 5 hospitals (3 governmental and 2 private) was surveyed in order to study their bacterial population including, total viable bacteria (TVB) and total coliform (TC) counts / ml, macro and micro-morphology of the isolated and identification of the isolated and purified bacterial strains to the specific level confirmed using API strips and its code index matching computer program. Counts allover the study showed figures beyond the international permissible limits, ranging between 1x 10 3 -1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 28 publications
0
8
1
Order By: Relevance
“…1). In an analogous study [15], conducted on final effluent of 5 hospitals in Al-Madina Al-Munnawara, the counts on plate count agar were ranging from 1.26x 10 4 /ml for Saudi German hospital wastewater to 1.25x 10 6 /ml for King Fahd hospital. In the same investigation, the average counts on MacConkey's agar ranged from 1.04x 10 3 /ml for Ohod hospital to 1.85x 10 5 /ml for King Fahd hospital.…”
Section: Resultsmentioning
confidence: 99%
“…1). In an analogous study [15], conducted on final effluent of 5 hospitals in Al-Madina Al-Munnawara, the counts on plate count agar were ranging from 1.26x 10 4 /ml for Saudi German hospital wastewater to 1.25x 10 6 /ml for King Fahd hospital. In the same investigation, the average counts on MacConkey's agar ranged from 1.04x 10 3 /ml for Ohod hospital to 1.85x 10 5 /ml for King Fahd hospital.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it is not uncommon to detect MDR organisms among these bacteria [7,8]. In this study, the prevalence of MDR Gram-negative bacteria in the wastewater of a hospital was examined as MDR organisms have been linked to outbreaks that cause a high threat to the community as a whole [6].…”
Section: Discussionmentioning
confidence: 99%
“…E. coli is the key determinant for fecal contamination in water and therefore would have been expected to be the most prevalent organism [25]. Another study conducted in several wastewater treatment plants in Gaza, Iraq and Saudi Arabia showed that E. coli was the most prevalent microorganism with the highest rates of antibiotic resistance [7,8,24,26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations